(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Raising a mentally and physically mature generation is not only a national need, but a matter of national importance - it is a noble goal for all brotherly peoples born and raised in multi-ethnic Uzbekistan. At this point, national and universal values, the best traditions of our rich spiritual heritage, and the new traditions that are being formed, become a powerful factor of education. In the process of enriching the heredity of our people, raising a mentally and physically healthy generation, a perfect human personality, a joint member of the family, state and society, is formed in a fair society - a man of the 21st century.